2023
DOI: 10.1002/pts.2762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermoforming operation and tooling on the thermoformability of plastic‐coated fibre‐based materials

Abstract: Advances in the three‐dimensional (3D) forming of fibre‐based materials require the formulation of more formable materials and the development of process lines, machinery, and tools. Using a thermoforming process to convert fibre‐based materials into 3D forms is an emerging area of research which requires further investigation into the practicality of the process line and tooling in forming such materials. Accordingly, this study evaluated the impact of the thermoforming process operation and tooling on the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The slight variation in the values obtained could be related to both the measurement error and nonuniformity of the surface flatness. In a previous investigation, it was observed that spring-back occurred during the thermoforming process of multilayer fiber-based composites [ 45 ]. However, the attainment of an identical depth as the mould for these mixed structure WPCs could indicate the absence of significant spring-back for this particular geometry and the employed process.…”
Section: Resultsmentioning
confidence: 99%
“…The slight variation in the values obtained could be related to both the measurement error and nonuniformity of the surface flatness. In a previous investigation, it was observed that spring-back occurred during the thermoforming process of multilayer fiber-based composites [ 45 ]. However, the attainment of an identical depth as the mould for these mixed structure WPCs could indicate the absence of significant spring-back for this particular geometry and the employed process.…”
Section: Resultsmentioning
confidence: 99%